ANALYSIS OF THE EFFECT OF WORK DISCIPLINE, WORK ENVIRONMENT, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. BAYUTAMA TEKNIK - Maswani, Maswani; Puji Utami, Elis; Nofiar, Nofiar (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The objective of this research is to the effect analysis of work discipline, work environment, and work motivation on employees performance at PT. Bayutama Teknik. The research methodology that applied for this research was quantitative method and primary data which obtained from questionnaries. This sampling technique uses the random sampling method. Multiple linear regressions was used as the data analysis technique to test the validity, reliability test, classic assumption test (normality test, multicolloniearity test, autocorrelation test, heteroscedasticity test), and hypothesis testing t-statistical and f-statistic in order to examine the collective effect with a significance level of 5%. The results of this study show that in partial variable motivation, work discipline, and work environment has a positive impact and a significant of employee performance at PT. Bayutama Teknik. Meanwhile, the independent variable of motivation, work discipline, and work environment simultaneously has a significant relationship to the dependent variable of employee performance at PT. Bayutama Teknik. Coefficient of determination from this study showed 51.1% result, while the remaining of 48.9% is affected by other independent variables.